2014
DOI: 10.1055/s-0034-1376968
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quercetin on Oxidative Stress Biomarkers in Methimazole – Induced Hypothyroid Rats

Abstract: The objective of the present study was to evaluate the effect of quercetin on oxidative stress biomarkers in methimazole (MMI) - induced hypothyroidism male rats. Hypothyroidism was induced by administering MMI at 20 mg/100 ml in the drinking water, for 1 month. After achieved hypothyroidism, rats received orally 10 or 25 mg/kg of quercetin (QT) for 8 weeks. 60 male wistar rats were randomly divided into 6 groups (group I, control; group II, QT10; group III, QT25; group IV, hypothyroid; group V, hypothyroid+QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…However, little is known about redox status after the cessation of developmental exposure to antithyroid agent. In adult rats, increase of oxidative stress in the brain sustains for at least 8 weeks after achieving hypothyroidism for 4 weeks by exposure to anti-thyroid agent (Santi et al, 2014). In the present study, we observed transcript upregulation of antioxidant enzyme genes, Gpx1, Gpx4, Gsta5, Nqo1, Prdx1 and Txn1, in the dentate gyrus at the adult stage after developmental hypothyroidism.…”
Section: Discussionsupporting
confidence: 64%
“…However, little is known about redox status after the cessation of developmental exposure to antithyroid agent. In adult rats, increase of oxidative stress in the brain sustains for at least 8 weeks after achieving hypothyroidism for 4 weeks by exposure to anti-thyroid agent (Santi et al, 2014). In the present study, we observed transcript upregulation of antioxidant enzyme genes, Gpx1, Gpx4, Gsta5, Nqo1, Prdx1 and Txn1, in the dentate gyrus at the adult stage after developmental hypothyroidism.…”
Section: Discussionsupporting
confidence: 64%
“…We established a model of sHT in rats by gavage with MMI and treated one group of sHT rats with LT 4 . The dosages of MMI and LT 4 were based on former studies ( 24 , 25 ), and different doses of MMI have been verified and adjusted to establish a rat model of sHT in a 4-month experiment. We determined TSH and T 4 levels to confirm that the sHT rat model was successful and that LT 4 treatment was effective.…”
Section: Discussionmentioning
confidence: 99%
“…After one week of environmental adaptation, rats were randomly divided into five groups: control euthyroid group ( n = 10), sHT A group ( n = 15), sHT B group ( n = 15), sHT C group ( n = 15) and sHT + T 4 group ( n = 10). In the sHT rats, groups A–C were separately induced by administration of 20 mg/kg/day methimazole (MMI), 30 mg/kg/day MMI and 40 mg/kg/day MMI once daily by gavage ( 13 , 23 , 24 ). The sHT + T 4 group was administered 20 mg/kg/day MMI once daily by gavage.…”
Section: Methodsmentioning
confidence: 99%
“…SCH rats were induced by MMI administration (10 mg/kg) once daily by gavage. This dose was selected based on previous studies[ 30 32 ], and we reduced the dose by five-fold. After 45 days, a rat model of SCH was established.…”
Section: Discussionmentioning
confidence: 99%